Comparison tests for the determination of the viscosity values of reference liquids by capillary viscometers and stabinger viscometer SVM 3001 - Sariyerli Gokce Sevim (International Journal of Metrology and Quality Engineering, 2018)
The present study was realized for measuring viscosities of reference liquids using capillary viscometers and Stabinger viscometer SVM 3001 with viscosity interval between 1 mm2/s and 5000 mm2/s with temperatures from 20 °C to 80 °C. Based on our measurement with various liquids, we determine the viscosity values and compare both of the results. The aim of this study to evaluate the results of the primary level viscosity measurement system and stabinger viscometer and to compare the measurement results due to the providing traceability of Stabinger viscometer by TUBITAK UME. An increasing number of national metrology institutes and accredited laboratories provide viscometer calibration with reference liquids in a wide viscosity range. It is a common practice to use the viscosity of water as the metrological basic of viscometry. The national standard of viscosity provided by TUBITAK UME consists of a set of ubbelohde viscometers covering the measuring range of kinematic viscosities from about 0.5 mm2/s to 100 000 mm2/s. At the low viscosity, long − capillary viscometers are used as primary standards which are directly calibrated water.